2019
DOI: 10.1002/jcb.29260
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 protects against pathological cardiac remodeling by modulating galectin‐3 expression

Abstract: Background/Aims: Fibroblast growth factor 21 (FGF21) plays a protective role in ischemia/reperfusion induced cardiac injury. However, the exact molecular mechanism of FGF21 action remains unclear. This study was designed the protective effect of FGF21 on the heart and its mechanism.Method: Adenovirus vector expressing FGF21 or control β-galactosidase was injected into the myocardium of mice. Myocardial injury was observed by tissue staining and immunohistochemical staining. The expression level of caspases-3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Presumably via different downstream effectors that regulate myocyte apoptosis, MEK1 transgenic mice and ERK2 hemizygous knock-out mice exhibit decreased and increased infarct size, respectively, after ischemia-reperfusion (Lips et al, 2004). Likewise, gain and loss of ERK1/2 signaling may explain the beneficial and deleterious effects on myocyte survival and infarct size of exogenous FGF21 and Fgf21 knock-out, respectively, in mice subjected to ischemia-reperfusion injury or permanent coronary artery ligation (Joki et al, 2015;Liu et al, 2013), although other ERK1/2-independent pathways may also be involved (Hu et al, 2018;Li et al, 2020b;Sun et al, 2019). This pro-survival signaling could complicate the targeting of FGF21-FGFR4 signaling in diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably via different downstream effectors that regulate myocyte apoptosis, MEK1 transgenic mice and ERK2 hemizygous knock-out mice exhibit decreased and increased infarct size, respectively, after ischemia-reperfusion (Lips et al, 2004). Likewise, gain and loss of ERK1/2 signaling may explain the beneficial and deleterious effects on myocyte survival and infarct size of exogenous FGF21 and Fgf21 knock-out, respectively, in mice subjected to ischemia-reperfusion injury or permanent coronary artery ligation (Joki et al, 2015;Liu et al, 2013), although other ERK1/2-independent pathways may also be involved (Hu et al, 2018;Li et al, 2020b;Sun et al, 2019). This pro-survival signaling could complicate the targeting of FGF21-FGFR4 signaling in diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FGF21 expression has been found to be increased in HFpEF patients with diastolic dysfunction (Chou et al, 2016). FGF21 appears to have direct effects on the heart, including cardio-protective actions of short-term FGF21 elevations during ischemia/reperfusion injury, β-adrenergic activation, or hypertension (Hu et al, 2018;Joki et al, 2015;Li et al, 2020b;Li et al, 2019;Liu et al, 2013;Patel et al, 2014;Planavila et al, 2013;Planavila et al, 2015a;Ruan et al, 2018;Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It can promote macrophage migration, cardiac fibroblast proliferation, and collagen deposition in the matrix, leading to reduced ejection fraction ( 104 ). FGF21 regulated Gal-3 levels in H9c2 cells in a dose-dependent manner and ECM-related proteins (fibronectin, collagen I) levels were also decreased under FGF21 treatment ( 105 ). This suggested that FGF21 may play a protective role in the heart by reducing the level of cardiac fibrosis through downregulating Gal-3 levels.…”
Section: Fgf21 In Cardiac Fibrosismentioning
confidence: 99%
“…In the H9c2 hypoxia/reoxygenation model, FGF21 can improve H9c2 cell I/R injury by promoting autophagy via different pathways, such as the FGF21-Beclin‑1/vacuolar protein sorting 34 proteins-autophagy pathway 73 and the FGF21-microRNA-145- autophagy pathway 72 . FGF21 can also decrease the expression levels of galectin-3 to alleviate hypoxia-induced cardiac myocyte injury in vivo 74 . In addition, FGF21 can improve the energy metabolism of H9c2 cells after I/R via the FGF21-angiopoietin-2-glucose transporter 1 pathway in vitro 75 .…”
Section: Fgf21 and Cvdmentioning
confidence: 99%